Ly6Chigh Monocytes Protect against Kidney Damage during Sepsis via a CX3CR1-Dependent Adhesion Mechanism - Chousterman, Benjamin G; Boissonnas, Alexandre; Poupel, Lucie; Baudesson de Chanville, Camille; Adam, Julien; Tabibzadeh, Nahid; Licata, Fabrice; Lukaszewicz, Anne-Claire; Lombès, Amélie; Deterre, Philippe; Payen, Didier; Combadière, Christophe (Journal of the American Society of Nephrology, 2016)
Monocytes have a crucial role in both proinflammatory and anti-inflammatory phenomena occurring during sepsis. Monocyte recruitment and activation are orchestrated by the chemokine receptors CX3CR1 and CCR2 and their cognate ligands. However, little is known about the roles of these cells and chemokines during the acute phase of inflammation in sepsis. Using intravital microscopy in a murine model of polymicrobial sepsis, we showed that inflammatory Ly6C(high) monocytes infiltrated kidneys, exhibited altered motility, and adhered strongly to the renal vascular wall in a chemokine receptor CX3CR1-dependent manner. Adoptive transfer of Cx3cr1-proficient monocyte-enriched bone marrow cells into septic Cx3cr1-depleted mice prevented kidney damage and promoted mouse survival. Modulation of CX3CR1 activation in septic mice controlled monocyte adhesion, regulated proinflammatory and anti-inflammatory cytokine expression, and was associated with the extent of kidney lesions such that the number of lesions decreased when CX3CR1 activity increased. Consistent with these results, the pro-adhesive I249 CX3CR1 allele in humans was associated with a lower incidence of AKI in patients with sepsis. These data show that inflammatory monocytes have a protective effect during sepsis via a CX3CR1-dependent adhesion mechanism. This receptor might be a new therapeutic target for kidney injury during sepsis.